Trichoscopy and LC-OCT findings in sonidegib-induced alopecia in patients with advanced basal cell carcinoma - Ciobotariu, Irina; Palmisano, Gerardo; Caldarola, Giacomo; Piccerillo, Alfredo; Tassone, Francesco; Cappilli, Simone; Di Stefani, Alessandro; Peris, Ketty (Dermatology reports, 2025)
Sonidegib is a Hedgehog pathway inhibitor (HHIs) used as first-line systemic treatment for patients with advanced basal cell carcinoma (aBCC). Alopecia is reported as a frequent adverse event (AE), occurring in 49% of patients. Forty-five patients with aBCC were treated with sonidegib between December 2022 and December 2023; among them, 11/45 patients developed alopecia. Trichoscopic features included yellow dots, black dots, exclamation mark hairs, and broken hairs. Upon LC-OCT examination, yellow dots were seen as dilated follicular dark spaces containing malted nonhomogeneous material and outlined by bright collarets; black dots corresponded to normal-sized follicular ostia filled with bright, homogeneous material and cadaverized hair; exclamation mark hairs were short dark dysmorphic hairs with a different size of proximal and distal end and broken hairs were short dysmorphic hairs. LC-OCT may provide additional insights of early signs and clinical evolution of sonidegib-induced alopecia in patients with aBCC.